Clinical and immunological features of primary and secondary antiphospholipid syndrome - T M Reshetnvak; T N Kotelnikova; L A Kalashnikova; T A Lisitsyna; E N Alexandrova; E S Mach; T L Tihonova; Z S Alekberova; V A Nassonova; A. V. Volkov; V A Nassonova; E L Nassonov (Научно-практическая ревматология)
Objective. Rertrospective analysis of clinical and laboratory features of primary (PAPS) and secondary (SAPS) antiphospholipid syndrome (APS) in systemic lupus erythematosus (SLE). Material and methods. 280 pts (96 male, 184 female) with SLE were included. 142 had SAPS and 84 (24 male, 60 female) - PAPS. Mean age was 31,2±ll,l years and mean disease duration - 8.6+7,2 years. PAPS pts mean age was 35,6±9,9 years and mean disease duration - 1 1,9±8,5 years. Peripheral vessels USDG and echocardiography (EchoCG) were performed to verify vascular complications. Anticardiolipin antibodies (АСА) and lupus anticoagulant (LA) served as serological markers of APS. Results. In 75% of pts the disease began with SLE signs, in 17% - with ARS signs and in 8% - with thrombocytopenia. 5 from 138 SLE pts without APS showed LA and APS clinical signs during follow- up. In 54% from 142 SAPS pts the disease began with an SLE sign, in 34% - with an APS sign and in 12% - with thrombocytopenia. At the onset of PAPS thrombocytopenia was much more seldom - in 5 from 84 pts. The rest had other APS signs at presentation. 8 pts showed PAPS transformation into SLE, Thrombotic complications frequency among SLE pts was 42%. They were significantly more frequent in APS (76% in PAPS and 90% in SAPS) than in SLE without APS (6%), x 2=I3I, p<0,000l. There was heart disease association with APS. Heart disease was present in 43% of PAPS pts, 27% of SLE+APS pts and only in 2% of SLE pts without APS. Neurological signs spectrum in PAPS and SLE+APS was similar but stroke in PAPS was significantly more frequent (46%) than in SAPS (26%). Digital necroses, nail bed infarctions and purpura, which probably develops with participation of inflammation, were not characteristic for PAPS. Conclusion. Our data shows difficulty of PAPS verification, possibility of its transformation into SAPS what proves necessity of clinical and laboratory monitoring for this pts category. Beside that despite of similarity of the two forms of APS some distinct features of PAPS and SAPS were revealed.